Altitudinal Influence on Soil Nutrient Availability in Apple Orchards of Dry Temperate Zone of Western Himalayas - Verma, Sudhir; Sharma, Swati; Dhiman, Sushil (International Journal of Economic Plants, 2025)
The study was conducted during september, 2022 to investigate the influence of altitudinal variation on soil nutrient status in apple orchards located in the Kalpa block of the dry temperate region of the Himalayas. Soil samples were systematically collected from apple orchards situated at different elevations and were thoroughly analysed for various key soil parameters, including soil pH, organic carbon, available nitrogen, phosphorus, potassium, exchangeable Ca and Mg, sulphate-sulphur and micronutrients content. The results revealed that soil pH remained near neutral across all elevations. However, a significant increase in the concentrations of soil organic carbon, available nitrogen, phosphorus, exchangeable Ca and micronutrients was observed with increasing elevation. This enrichment at higher altitudes was largely attributed to lower ambient temperatures, which slowed down microbial activity and decomposition processes, thereby enhancing organic matter accumulation and nutrient retention in the soil. Conversely, the availability of potassium and sulphate-sulphur was found to be higher at lower elevations. This could have resulted from more intense mineral weathering, higher soil temperatures, and the relatively greater use of agrochemicals in lower orchards compared to those situated at higher altitudes. These altitudinal trends emphasized the critical role of elevation in shaping soil fertility dynamics. The study provided valuable insights for the development of location-specific and altitude responsive nutrient management strategies, which are essential for optimizing apple yield and maintaining long term soil health in the ecologically sensitive and climatically diverse Himalayan agroecosystems.